14-Noreudesmanes and a phenylpropane heterodimer from sea buckthorn berry inhibit Herpes simplex type 2 virus replication. Issue 10 (8th March 2019) - Rédei, Dóra; Kúsz, Norbert; Rafai, Tímea; Bogdanov, Anita; Burián, Katalin; Csorba, Attila; Mándi, Attila; Kurtán, Tibor; Vasas, Andrea; Hohmann, Judit
Abstract: Two new 14-noreudesmane sesquiterpenes, one new phenylpropane heterodimer, caulilexin C, and uvaol were isolated from the 70% MeOH extract of the fruit peel of Elaeagnus rhamnoides . The structures of the compounds were elucidated by HRESIMS and advanced NMR methods. The absolute configuration of ( R )-6, 9-dihydroxy-1-oxo-14-noreudesm-5, 7, 9-triene was determined by the TDDFT-ECD method. The new compounds, together with structurally similar naphthalenes (musizin, musizin-8- O -glucoside, torachrysone-8- O -glucoside) and 1, 4-naphthoquinone (2-methylstipandrone), isolated previously from Rumex aquaticus, were investigated for their antiviral activity against Herpes simplex virus type 2 (HSV-2) using two different methods. Applying the traditional virus yield reduction test, ( R )-6, 9-dihydroxy-1-oxo-14-noreudesm-5, 7, 9-triene, 1-[3-methoxy-4-(2-methoxy-4-(1 E )-propenyl-phenoxy)-phenyl]-propane-1, 2-diol, and musizin caused a 2.00 log10, 3.49 log10, and 2.33 log10 reduction of HSV-2 yield, respectively, at a concentration of 12.5 μM. 2-Hydroxy-1-methoxy-6, 9-dioxo-14-noreudesm-1, 3, 5(10), 7-tetraene exhibited an antiviral effect at concentration of 50 μM only. Similar results were obtained when the qPCR method was used to test the antiviral activity of the compounds. Graphical abstract: Image 1